Competitividad de la agroindustria aceitunera de Tacna en tiempos de pandemia COVID-19 - Palma Leva, Marisol (2021)
The objective of the research was to determine the impacts by the confinement caused by COVID-19 on the competitiveness of olive agribusiness in Tacna in 2020, identifying the effects caused on productivity, quality, human resources, managerial practices, sales and market access, installed capacity and environmental performance. The methodology is descriptive and transversal, the study population consisted of companies of the field olives that classify as: Natural Person, Micro, Small and Medium-sized company dedicated to the field of table olives and oil production. The collection of information took place between September and November in 2020 for this purpose the survey technique was used, developed an instrument with 70 % reliability (Alpha crombach) consisting of 37 questions that were re-categorized in dimensions. The results indicate that there were no significant impacts on dimensions and analyzed using the non-parametric test of Chi square, kruskal wallis and Games-Howell: productivity level; sales level; access and market access; management practices and business articulation; production quality, human resources and environmental performance with a 95 % confidence level, however when comparing between types of companies natural people with businesses were found to have negative impacts on specific aspects such as: volume of exports; training carried out on staff; financial and accounting control tools and in the application of organizational techniques that are applicable in management, all at 95 % confidence. It is therefore concluded that there were no impacts caused by COVID-19 confinement. On the competitiveness of olive agribusiness in Tacna in 2020.